The stigmatisation of widows and divorcees (janda) in Indonesia, and the possibilities for agency. Issue 128 (2nd January 2016) - Parker, Lyn; Riyani, Irma; Nolan, Brooke
ABSTRACT: This article explores the discourses and practices of stigmatisation that shape the experience of widows and divorced women ( janda ) in Indonesia. The conceptualisation of stigma allows us to see that the experience of being a janda is a gendered, moral experience. The article examines the construction of ideal marriage in Islam and in Indonesia, divorce, and the construction of gender and sexuality. There is a dominant discourse that divorced and widowed women are sexually available and promiscuous; the result is often that men prey upon janda . In turn, wives feel threatened by the competition that janda represent. This article is based on ethnographic and interview data from two field sites: Bandung, West Java, and Wawonii island, off the coast of Southeast Sulawesi; both are Muslim communities. It also explores the possibilities for women's agency and destigmatisation, through the mobilising of social networks and the emphasising of their worth as good mothers to achieve social respectability.